Evaluation of Sidr Leaf Ethanol (Ziziphus mauritiana Lam.) Extract-Based Tablets as Antihypercholesterolemia - Orbayinah, Salmah; Dewi, Yunita P.; Kurniawan, Fariez; Krisridwany, Annisa (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Sidr leaf extract (Ziziphus mauritiana Lam.) is effective against hypercholesterolemia by blocking the HMG-CoA reductase. This study seeks to identify the characteristics of tablets formulated from the ethanol extract of Sidr leaf and their efficacy in lowering total blood cholesterol levels. The tablets were produced using the wet granulation method and processed into three formulations, F1, F2, and F3, with differing dosages of 100, 150, and 250 mg, along with placebo. The granules produced were evaluated for their physical characteristics. The tablets were evaluated for their physical characteristics and tested for effectiveness in lowering cholesterol levels. The efficacy of tablet-form sidr leaf ethanol extract was assessed by analyzing cholesterol levels in mouse serum samples compared to simvastatin. The data were statistically analyzed using one-way ANOVA and post-hoc Tukey HSD test. In the disintegration time test, F1 and F2 tablets satisfied the criteria. However, F3 exceeded the limit of 60 minutes. Among the three tablet doses, the F2 tablet (150 mg) demonstrated superior efficacy in lowering total cholesterol levels relative to the F1 and F3 tablets. Consequently, tablets containing Sidr leaf extract demonstrate potential for hypercholesterolemia management at an effective dosage of 150 mg, warranting further investigation through clinical trials.